Patricia W. Romero, African Women: A Historical Panorama (Historia, 2021)
In African Women: A Historical Panorama, Patricia W. Romero seeks to address what she perceives as a gap in existing scholarship on the history of African women, namely a lack of personalisation and case studies in accounts of women who have made important interventions in the historical narratives of Africa. While recognising the many high quality works by noted historians, Romero introduces her text by expressing her desire to “produce a different type of book” {p ix). This is something she certainly accomplishes because her text deviates somewhat from most historical scholarship in terms of its style and format. Her focus throughout the work is indeed on the women whose personal stories and contributions she wants to bring into sharper relief in academic conversations. As her title suggests, the view she provides on African women is a panoramic one that encompasses pre-colonial, colonial as well as post-colonial African history. The attempt to combine a panoramic overview with a focus on personal stories is a challenging task that Romero has set herself but, I would argue, she manages to produce a text that adds value to our academic understandings of African women’s roles in history.Given the subject matter, the author is obliged to pay considerable attention to the myriad forms of epistemic, socio-political and economic oppression that have shaped the narratives of women on the African continent and continue to do so. Without shying away from the reality of gendered oppression, Romero never loses sight of women’s resilience and the creative ways in which they exercise agency, even in contexts of severe structural disempowerment. This commitment to celebrating African women’s strength is reflected in the chapter delineation with Chapter One dealing with “Pre-colonial Queens and Powerful Women” and the final chapter being entitled “The March of the Women”. This last chapter is devoted to African women’s vital contributions in spheres ranging from literature to fashion and sport. By beginning and ending her text with celebratory stories of women’s power and accomplishments, the author cushions the necessary but difficult discussion on topics such as female genital mutilation and gender violence in times of war.
Keywords: book reviews